An Adaptable Paw Design for Quadruped Robots Operation in Mining Environments - Barros, Luiz Guilherme Dias de; Cid, André Luiz Maciel; Domingues, Jacó Dias; Medeiros, Vivian Suzano; Pessin, Gustavo; Becker, Marcelo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Robotic devices have witnessed a growing deployment in operational settings where human safety is at risk, notably in confined spaces such as inspecting dam galleries and monitoring the load of grinding media in ball mills. Many difficulties faced in these operations are related to robot locomotion systems. Legged robots can overcome obstacles easier than other models with wheels and tracks, and adapting the control according to the soil can improve the chance of successfully completing the task. One way to improve the control system is to use a force-torque (F/T) sensor coupled to the paw working as feedback to have a tactile response in different soil contacts. Thus, this paper presents the development of a mechanical design of an adaptable paw with support springs and rotating pins for the Solo12 robot. The proposed design includes a force-torque sensor and a joint between the F/T to enhance adaptability by allowing small roll-pitch rotations. Despite the paw mass increase of almost 80 % compared with the original one, it is expected that it does not influence the performance and functions of the robot. The components were mechanically validated by simulation, and future work should implement the proposal on a real simulator to compare the efficiency of the robot control system in both ways: with and without this proposal.